Separation of Herpes Simplex Virus-Induced Antigens by Concanavalin A Affinity Chromatography - De Leon, Manuel Ponce (1973)
Biologically active herpes simplex virus (HSV)-induced antigens were selectively removed from extracts of infected BHK cells by affinity chromatography by utilizing an insoluble form of concanavalin A (Con A). Soluble extracts of (3)H-glucosamine-labeled, HSV-infected cells were absorbed to a Con A column. Bound material was eluted with α-methyl-d-mannoside (αMM) and NaCl. The specific activity of the eluted glycoproteins increased by 10-fold. Two broad groups of viral-induced antigens were isolated from Con A. Group I includes two antigens which bind to Con A by a specific mechanism because the antigens are dissociated by αMM. Group II contains three antigens which bind to Con A but apparently by a nonspecific or electrolytic mechanism. One antigen in group I was identified as the glycoprotein antigen, CP-1, described previously.